2007
DOI: 10.1002/rcm.2994
|View full text |Cite
|
Sign up to set email alerts
|

Beam‐type collisional activation of polypeptide cations that survive ion/ion electron transfer

Abstract: Doubly protonated peptides that undergo an electron transfer reaction without dissociation in a linear ion trap can be subjected to beam-type collisional activation upon transfer from the linear ion trap into an adjacent mass analyzer, as demonstrated here with a hybrid triple quadrupole/linear ion trap system. The activation can be promoted by use of a DC offset difference between the ion trap used for reaction and the ion trap into which the products are injected of 12-16 V, which gives rise to energetic col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 27 publications
(25 reference statements)
0
39
0
Order By: Relevance
“…Beam-type CID experiments were performed using the same instrument. The experimental procedures for ion parking and beam-type CID used here have been reported in detail elsewhere [50,51]. In brief, the following experimental sequence was used: 1) cation accumulation (200–250 ms) in Q0; 2) ion parking in Q0 (to obtain low charge state species); 3) precursor ion isolation via Q1; 4) beam-type CID in Q2 with the injection energy determined by the DC rod offset difference between Q0 and Q2; 5) mutual storage mode ion-ion reactions in Q2; and 6) mass analysis of ions using a reflectron time-of-flight mass analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…Beam-type CID experiments were performed using the same instrument. The experimental procedures for ion parking and beam-type CID used here have been reported in detail elsewhere [50,51]. In brief, the following experimental sequence was used: 1) cation accumulation (200–250 ms) in Q0; 2) ion parking in Q0 (to obtain low charge state species); 3) precursor ion isolation via Q1; 4) beam-type CID in Q2 with the injection energy determined by the DC rod offset difference between Q0 and Q2; 5) mutual storage mode ion-ion reactions in Q2; and 6) mass analysis of ions using a reflectron time-of-flight mass analyzer.…”
Section: Methodsmentioning
confidence: 99%
“…, higher m/z values). 3739 As precursor m/z values increase, so increases the likelihood of non-dissociative electron transfer (ETnoD), 40 a process in which backbone bond cleavage occurs but the fragment ions remain bound together by non-covalent interactions. ETnoD reduces precursor-to-product ion conversion, limiting the sequence information gleaned from an ETD MS/MS event.…”
Section: Introductionmentioning
confidence: 99%
“…For example, McLafferty et al developed activated ion ECD, a method combining electron capture and collisional activation, to increase sequence coverage for top-down proteomics applications [30]. Both the Coon [27] and McLuckey groups [31,32] have developed methods that combine electron activation with subsequent collisional activation of the charge-reduced ions (in a tandem process sometimes abbreviated as ETcaD), resulting in improved sequence coverage for peptides in low charge states. Our group also reported that ETcaD of N-terminal derivatized peptides afforded simplified MS/MS spectra containing predominantly C-terminal z-type ions, leading to successful de novo sequencing of peptides [33].…”
Section: Introductionmentioning
confidence: 99%